Assessment of Complex Problem Solving: What We Know and What We Don't Know. Issue 4 (1st October 2016) - Herde, Christoph Nils; Wüstenberg, Sascha; Greiff, Samuel
ABSTRACT: Complex Problem Solving (CPS) is seen as a cross-curricular 21st century skill that has attracted interest in large-scale-assessments. In the Programme for International Student Assessment (PISA) 2012, CPS was assessed all over the world to gain information on students' skills to acquire and apply knowledge while dealing with nontransparent problem situations. This review article summarizes current developments in the assessment of CPS using multiple complex systems and focuses on four topics: (a) What is CPS and why is it relevant, (b) What do we know about CPS, (c) What do we gain from its assessment, and (d) What there is to come. More specifically, we (a) elaborate on how changes in today's world call for the assessment of CPS, (b) summarize recent empirical results on CPS, pinpoint how log file analyses of students' behavioral data (c) help to understand differences in CPS, and (d) may deepen the understanding of CPS.